أثر الالتزام بمنهج سيجما ستة "Six sigma" في تحسين الأداء المؤسسي من وجهة نظر العاملين في المصارف الحكومية بمحافظة دمشق - شدود، كنان (جامعة البعث, 2023)
هدف البحث إلى تعرف درجة تطبيق منهج سيجما ستة من وجهة نظر العاملين في المصارف الحكومية بمحافظة دمشق. ومستوى الأداء المؤسسي في المصارف الحكومية. والعلاقة بين درجة تطبيق منهج سيجما ستة والأداء المؤسسي. وأيضا تعرف دلالة الفروق في إجابات أفراد عينة البحث على استبانة منهج سيجما ستة وعلى استبانة الأداء المؤسسي وفق متغيري البحث: (سنوات الخبرة، المؤهل العلمي). واعتمد في هذا البحث على المنهج الوصفي التحليلي، واستخدم أداتي البحث: (استبانة تطبيق منهج سيجما ستة، واستبانة الأداء المؤسسي). وشملت عينة البحث (382) عاملا وعاملة في المصارف الحكومية بمحافظة دمشق. ومن أهم النتائج التي توصل إليها البحث: وجود علاقة ارتباطية إيجابية ذات دلالة إحصائية بين درجة تطبيق منهج سيجما ستة وبين الأداء المؤسسي في المصارف الحكومية. ووجود فروق ذات دلالة إحصائية بين متوسط درجات أفراد عينة البحث على استبانة درجة تطبيق منهج سيجما ستة واستبانة الأداء المؤسسي وفق متغير المؤهل العلمي لصالح الأفراد الذين يمتلكون مؤهل علمي (دبلوم فأعلى). وعدم وجود فروق ذات دلالة إحصائية بين متوسط درجات أفراد عينة البحث على استبانة درجة تطبيق منهج سيجما ستة واستبانة الأداء المؤسسي وفق متغير سنوات الخبرة. The objective of the research is to define the level of degree of application of Six Sigma approach from the point of view of the employees of the governmental banks in Damascus Governorate. And the level of institutional performance in government banks. The relationship between the degree of application of Six Sigma curriculum and institutional performance. The significance of the differences in the responses of the individuals in the research sample is also known as the Six Sigma method and the institutional performance according to the two research variables: (years of experience, qualification). In this research, the analytical descriptive approach was adopted and the research tools were used: (Six Sigma Methodology and the Institutional Performance Questionnaire). The sample included (382) workers working in government banks in Damascus Governorate. The existence of a positive correlative correlation between the degree of application of the Six Sigma approach and the institutional performance in government banks. And the existence of statistically significant differences between the average scores of the sample of the research sample to determine the degree of application of Six Sigma approach and identify the institutional performance according to the variable qualification for the benefit of individuals who have a scientific qualification (Diploma and above). And the absence of statistically significant differences between the average scores of the members of the research sample to determine the degree of application of the Six Sigma approach and to identify the institutional performance according to the variable years of experience.
Keywords: التخطيط الاستراتيجي -- الأداء المؤسسي -- الإصلاح الاقتصادي -- الأداء الوظيفي